Video recording of broken ice floes from Observation of anomalous spectral downshifting of waves in the Okhotsk Sea Marginal Ice Zone - Takuji Waseda; Alberto Alberello; Takehiko Nose; Takenobu Toyota; Tsubasa Kodaira; Yasushi Fujiwara (2022)
Waves in the Marginal Ice Zone in the Okhotsk Sea are less studied compared to the Antarctic and Arctic. In February 2020, wave observations were conducted for the first time in the Okhotsk Sea, during the observational program by Patrol Vessel Soya. A wave buoy was deployed on the ice, and in situ wave observations were made by a ship-borne stereo imaging system and Inertial Measurement Unit. Sea ice was observed visually and by aerial photographs by drone, while satellite synthetic aperture radar provided basin-wide spatial distribution. On 12 February, a swell system propagating from east northeast was detected by both the stereo imaging system and the buoy-on-ice. The wave system attenuated from 0.34 m significant wave height to 0.25 m in about 90 km, while the wave period increased from 10 s to 15–17 s. This anomalous spectral downshifting was not reproduced by numerical hindcast and by applying conventional frequency-dependent exponential attenuation to the incoming frequency spectrum. The estimated rate of spectral downshifting, defined as a ratio of momentum and energy losses, was close to that of uni-directional wave evolution accompanied by breaking dissipation: this indicates that dissipation-driven nonlinear downshifting may be at work for waves propagating in ice.This article is part of the theme issue 'Theory, modelling and observations of marginal ice zone dynamics: Multidisciplinary perspectives and outlooks'.